Particles containing aluminum alloys
Patent Information
- Application Number
- JP2020202262
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-04
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2040-12-04
AI Technical Summary
【0013】 本発明では、一次粒子の形態で、二種類のアルミニウム合金の混合相を有する粒子を提供することができる。
Smart Images

Figure 0007644922000009 
Figure 0007644922000010 
Figure 0007644922000011
Abstract
Description
[Technical field]
[0001] The present invention relates to particles comprising an aluminum alloy. [Background technology]
[0002] In general, aluminum alloy powder has characteristics such as high specific strength and good resistance to various environments, and is therefore in demand for various applications.
[0003] Generally, aluminum alloy powder is produced by an atomization method (Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 1-108305 [Patent Document 2] International Publication No. WO2018 / 116856 Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, there has been an increasing need for particles containing two aluminum alloy phases with different compositions in binary MAl alloys (M is a metal other than aluminum).
[0006] For example, increasing the amount of aluminum contained in the aluminum alloy particles improves the corrosion resistance and chemical resistance such as high-temperature oxidation resistance, but tends to decrease the ductility. Conversely, decreasing the amount of aluminum contained in the aluminum alloy particles improves the ductility, but decreases the chemical resistance such as corrosion resistance and high-temperature oxidation resistance.
[0007] In contrast, if it is possible to combine an alloy phase having a low aluminum concentration (first aluminum alloy phase) with an alloy phase having a high aluminum concentration (second aluminum alloy phase), it is possible to provide alloy particles that are ductile and also have excellent chemical resistance.
[0008] From this perspective, Patent Document 2 proposes a powder containing an FeAl phase and an FeAl2 phase. In this case, it is possible to obtain an alloy powder that combines the characteristics of both the FeAl2 phase, which has excellent oxidation resistance, and the FeAl phase, which has ductility.
[0009] However, the alloy powder described in Patent Document 2 is provided in the form of secondary particles obtained by sintering together granulated powders of primary particles containing an aluminum alloy powder and an iron-based powder.
[0010] Such secondary particles require a complicated manufacturing process and may be subject to crushing during handling, which may result in the mixture of particles with various compositions and reduced particle uniformity.
[0011] The present invention has been made in view of the above background, and an object of the present invention is to provide particles having a mixed phase of two types of aluminum alloys in the form of primary particles. [Means for solving the problem]
[0012] In the present invention, a particle containing an aluminum alloy is provided, In the state of primary particles, It is approximately spherical, Composition M x Al y Phase represented by, and M z Al w where M is a metal other than Al, and <x<1、0<y<1、0<z<1、0<w<1であり、x / y≧1、z / w<1であり、x+y=1、z+w=1であり、 Particles are provided having an aluminum content in the range of 8% to 50% by mass. Effect of the Invention
[0013] In the present invention, it is possible to provide particles having a mixed phase of two types of aluminum alloys in the form of primary particles. [Brief description of the drawings]
[0014] [Figure 1] FIG. 2 is a schematic diagram showing a cross section of a particle according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing a cross section of a particle according to another embodiment of the present invention. [Diagram 3] FIG. 2 is a diagram showing a schematic example of a flow of a method for producing particles according to an embodiment of the present invention. [Figure 4] FIG. 2 is a diagram showing a schematic diagram of mixed particles filled in a reaction vessel. [Diagram 5] FIG. 2 is a diagram showing (a) a cross section of a particle obtained in one embodiment of the present invention, and (b) the distribution of aluminum contained in the cross section. [Figure 6] FIG. 2 shows (a) a cross section of a particle obtained in another embodiment of the present invention, and (b) a distribution of aluminum contained in the cross section. [Figure 7] FIG. 2 is a diagram showing (a) a cross section of a particle obtained in yet another embodiment of the present invention, and (b) the distribution of aluminum contained in the cross section. [Figure 8] FIG. 2 is a diagram showing (a) a cross section of a particle obtained in yet another embodiment of the present invention, and (b) the distribution of aluminum contained in the cross section. [Figure 9] FIG. 2 is a diagram showing (a) a cross section of a particle obtained in yet another embodiment of the present invention, and (b) the distribution of aluminum contained in the cross section. [Figure 10] FIG. 2 is a diagram showing (a) a cross section of a particle obtained in yet another embodiment of the present invention, and (b) the distribution of aluminum contained in the cross section. [Figure 11]FIG. 2 is a diagram showing (a) a cross section of a particle obtained in yet another embodiment of the present invention, and (b) the distribution of aluminum contained in the cross section. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, one embodiment of the present invention will be described.
[0016] As described above, there is a need for particles of MAl binary alloy (M is a metal other than aluminum) containing two types of aluminum alloy phases with different compositions. In order to address this need, Patent Document 2 describes secondary particles containing two types of aluminum alloy phases.
[0017] However, the secondary particles require a complicated manufacturing process and may be crushed during handling, which may result in the mixture of particles with various compositions and reduced particle uniformity.
[0018] In contrast, in one embodiment of the present invention, a particle containing an aluminum alloy is In the state of primary particles, It is approximately spherical, Composition M x Al y The phase represented by, and M z Al w where M is a metal other than Al, and <x<1、0<y<1、0<z<1、0<w<1であり、x / y≧1、z / w<1であり、x+y=1、z+w=1であり、 Particles are provided having an aluminum content in the range of 8% to 50% by mass.
[0019] The particles according to one embodiment of the present invention have the composition M x Al y and a phase represented by the formula (hereinafter referred to as the "first aluminum alloy phase") having a composition of M z Al wHereinafter, the second aluminum alloy phase includes a phase represented by the formula: <x<1、0<y<1、0<z<1、0<w<1であり、x / y≧1、z / w<1であり、x+y=1、z+w=1である。
[0020] The particles according to one embodiment of the present invention have a "first aluminum alloy phase" with a lower aluminum content and a "second aluminum alloy phase" with a higher aluminum content. Therefore, in one embodiment of the present invention, it is possible to provide particles that have both good ductility derived from the "first aluminum alloy phase" and good corrosion resistance and high-temperature oxidation resistance derived from the "second aluminum alloy phase".
[0021] Furthermore, the particles according to one embodiment of the present invention may be provided in the form of primary particles.
[0022] Therefore, the particles according to one embodiment of the present invention can be produced without going through a complicated production process as in the case of the secondary particles described in Patent Document 2. Furthermore, the particles according to one embodiment of the present invention can reduce or eliminate the problem of the particles being crushed during handling, resulting in reduced uniformity of the particles.
[0023] The particles according to one embodiment of the invention are generally spherical.
[0024] In this application, "substantially spherical" or "substantially spherical" is not limited to a pure sphere, but includes shapes such as ellipses, in which the dimensional difference in the mutually perpendicular X-axis and Y-axis directions is within ±20%.
[0025] The particles according to one embodiment of the present invention may have an average particle size in the range of 5 μm to 600 μm, preferably in the range of 8 μm to 200 μm, more preferably in the range of 10 μm to 150 μm.
[0026] The average particle size of the particles according to one embodiment of the present invention is measured by the method specified in JIS Z 8801, as described below.
[0027] Specific Examples of Particles According to an Embodiment of the Invention Hereinafter, specific examples of particles according to one embodiment of the present invention having the above-mentioned characteristics will be described.
[0028] (iron-aluminum alloy particles) The particles according to an embodiment of the present invention may be iron-aluminum alloy particles. In this case, for example, the first aluminum alloy phase M x Al y is FeAl, the second aluminum alloy phase M z Al w is FeAl2.
[0029] The aluminum concentration in all the primary particles is, for example, in the range of 32% by mass to 48% by mass.
[0030] (Chromium-aluminum alloy particles) The particles according to an embodiment of the present invention may be chromium-aluminum alloy particles. In this case, for example, the first aluminum alloy phase M x Al y is Cr2Al, the second aluminum alloy phase M z Al w is Cr5Al8.
[0031] The aluminum concentration in all the primary particles is, for example, in the range of 22% by mass to 42% by mass.
[0032] (Nickel-aluminum alloy particles) The particles according to an embodiment of the present invention may be nickel-aluminum alloy particles. In this case, for example, the first aluminum alloy phase M x Al y is NiAl, the second aluminum alloy phase M z Al w is Ni2Al3.
[0033] The aluminum concentration in all the primary particles is, for example, in the range of 36% by mass to 39% by mass.
[0034] (Molybdenum-aluminum alloy particles) The particles according to an embodiment of the present invention may be molybdenum-aluminum alloy particles. In this case, for example, the first aluminum alloy phase M x Al y is Mo3Al, the second aluminum alloy phase M z Al w is Mo3Al8.
[0035] The aluminum concentration in all the primary particles is, for example, in the range of 8% by mass to 42% by mass.
[0036] (Copper-aluminum alloy particles) The particles according to an embodiment of the present invention may be copper-aluminum alloy particles. In this case, for example, the first aluminum alloy phase M x Al y is CuAl, and the second aluminum alloy phase M z Al w is CuAl2.
[0037] The aluminum concentration in the entire primary particles is, for example, in the range of 30% by mass to 45% by mass.
[0038] (Manganese-aluminum alloy particles) The particles according to an embodiment of the invention may be manganese-aluminum alloy particles, for example, in which case the first aluminum alloy phase M x Al y is Mn3Al2, the second aluminum alloy phase M z Al w is Mn5Al8.
[0039] The aluminum concentration in all the primary particles is, for example, in the range of 25% by mass to 34% by mass.
[0040] An example of the material system of the particles according to the embodiment of the present invention has been described above. However, the above material system is merely an example, and the particles according to the embodiment of the present invention may have other material systems. For example, the particles according to the embodiment of the present invention may be tungsten-aluminum based, cobalt-aluminum based, platinum-aluminum based, hafnium-aluminum based, or zirconium-aluminum based.
[0041] Additionally, a number of the above material systems may be combined to form a particle according to an embodiment of the present invention.
[0042] For example, a particle according to an embodiment of the invention may be an iron-chromium-aluminium alloy particle, in which case the particle according to an embodiment of the invention may include, for example, Cr2Al and Cr5Al8 in addition to FeAl and FeAl2.
[0043] Particles according to one embodiment of the present invention Next, the morphology of particles according to one embodiment of the present invention will be described with reference to the drawings.
[0044] Here, as an example, a case where the particles are iron-aluminum alloy particles will be described.
[0045] FIG. 1 shows a schematic cross section of a particle according to one embodiment of the present invention (hereinafter referred to as a "first particle").
[0046] The cross section of the first particle shown in FIG. 1 is the "maximum cross section". In this application, the "maximum cross section" means a cross section passing through the center of the particle. For example, if the particle is spherical, the "maximum cross section" has substantially the same dimension as the diameter of the particle.
[0047] As shown in FIG. 1, the first particle 100 has a generally spherical shape.
[0048] The cross section (maximum cross section; the same applies below) of the first particle 100 has two regions with different aluminum concentrations. Hereinafter, the region with the relatively low aluminum concentration will be referred to as the "first region 110," and the region with the relatively high aluminum concentration will be referred to as the "second region 120."
[0049] 1, the core of the first particle 100 constitutes a first region 110, and the outer layer constitutes a second region 120. The second region 120 is disposed so as to surround the first region 110.
[0050] In the example shown in FIG. 1, the boundary between the first region 110 and the second region 120 is depicted by a clear line, but it is often the case that the boundary between the two is unclear.
[0051] The aluminum concentration in the entire cross section of the first particle 100 is in the range of 32 wt % to 48 wt %. The aluminum concentration may be, for example, in the range of 35 wt % to 45 wt %.
[0052] The iron concentration in the entire cross section of the first particle 100 may be, for example, in the range of 52 wt% to 68 wt%. However, the iron concentration will be lower than this range if the first particle 100 further contains elements described below.
[0053] The concentrations of aluminum and iron contained throughout the cross section of the first particle 100 can be measured by energy dispersive X-ray (EDX) analysis or electron probe microanalyzer (EPMA) analysis.
[0054] The first particle 100 may contain an element other than iron and aluminum (hereinafter, referred to as a "third element") The third element includes, for example, at least one of phosphorus, sulfur, and carbon.
[0055] The third element may be contained in a range of 0.05 wt% to 1 wt% in total. When the first particle 100 contains the third element, the iron concentration is the aforementioned range (52 wt% to 68 wt%) minus the concentration of the third element. In other words, the third element is present as a substitute element for iron or as an inevitable impurity.
[0056] The first region 110 of the first particle 100 mainly contains an FeAl phase. The concentration of aluminum contained in the first region 110 is in the range of 22 wt% to 37 wt%. The concentration of aluminum may be in the range of 25 wt% to 35 wt%, for example.
[0057] On the other hand, the second region 120 of the first particle 100 mainly contains a mixed phase of FeAl phase and FeAl2 phase. The aluminum concentration contained in the second region 120 is in the range of 40wt% to 50wt%. The aluminum concentration may be, for example, in the range of 42wt% to 48wt%.
[0058] The aluminum concentrations in the first region 110 and the second region 120 of the first particle 100 can be measured by EDX analysis or EPMA analysis of selected portions. Also, the constituent phases contained in each of the first region 110 and the second region 120 can be identified by X-ray diffraction analysis.
[0059] The proportion of the area occupied by the second region 120 in the cross section of the first particle 100 is, for example, 5% or more. Note that this area proportion can be evaluated by binarizing and defining the contrast of the Al concentration using an SEM backscattered electron image of the cross section.
[0060] Although the first particle 100 is a primary particle, it has a "first aluminum alloy phase" and a "second aluminum alloy phase". Therefore, the first particle 100 can have both good ductility derived from the "first aluminum alloy phase" and good corrosion resistance and high-temperature oxidation resistance derived from the "second aluminum alloy phase".
[0061] In addition, since the first particles 100 are primary particles, the problem of the particles being crushed during handling, resulting in a decrease in uniformity of the particles, can be reduced or eliminated.
[0062] Particles according to another embodiment of the present invention Next, referring to FIG. 2, a particle according to another embodiment of the present invention will be described.
[0063] Figure 2 shows a schematic cross-section of a particle according to another embodiment of the present invention (hereinafter referred to as "second particle"). As described above, the cross-section shown in Figure 2 is the "maximum cross-section" of the second particle.
[0064] 2, the second particle 200 has a substantially spherical shape. In addition, the cross section of the second particle 200 has two regions with different aluminum concentrations.
[0065] However, in the case of the second particle 200, unlike the first particle 100 described above, the second regions are "patterned" throughout.
[0066] That is, in the second particle 200, the second regions 220 having a relatively high aluminum concentration are distributed in an "island-like" manner in the "sea" of the first regions 210 having a relatively low aluminum concentration.
[0067] In other words, the entire cross section of the second particle 200 is composed of the "sea-like" first region 210 and the "island-like" second region 220. In the case of the second particle 200, both the first region 210 and the second region 220 are present even on the outermost surface.
[0068] The second particle 200 contains iron and aluminum, and the concentration of aluminum contained in the entire cross section of the second particle 200 is in the range of 32 wt% to 48 wt%. The concentration of aluminum may be, for example, in the range of 35 wt% to 45 wt%.
[0069] The iron concentration in the entire cross section of the second particle 200 may be, for example, in the range of 52 wt% to 68 wt%. However, as described above, the iron concentration will be lower than this range if the second particle 200 contains a third element.
[0070] The first region 210 of the second particle 200 mainly contains an FeAl phase. The concentration of aluminum contained in the first region 210 is in the range of 22 wt% to 37 wt%. The concentration of aluminum may be in the range of 25 wt% to 35 wt%, for example.
[0071] On the other hand, the second region 220 of the second particle 200 mainly contains a mixed phase of FeAl phase and FeAl2 phase. The aluminum concentration in the second region 220 is in the range of 40wt% to 50wt%. The aluminum concentration may be in the range of 42wt% to 48wt%, for example.
[0072] In the cross section of the second particle 200, the proportion of the area occupied by the second region 220 is, for example, 5% or more.
[0073] Although the second particles 200 are primary particles, they have a "first aluminum alloy phase" and a "second aluminum alloy phase". Therefore, the second particles 200 can have both good ductility derived from the "first aluminum alloy phase" and good corrosion resistance and high-temperature oxidation resistance derived from the "second aluminum alloy phase".
[0074] In addition, since the second particles 200 are primary particles, the problem of the particles being crushed during handling, resulting in a decrease in uniformity of the particles, can be reduced or eliminated.
[0075] The features of the particles according to one embodiment of the present invention have been described above using the first particle 100 and the second particle 200 as examples.
[0076] However, the first particle 100 and the second particle 200 are merely examples, and particles according to an embodiment of the present invention may have different morphologies.
[0077] For example, a particle according to one embodiment of the present invention may have a particle morphology that combines the particle morphology shown in FIG. 1 and the particle morphology shown in FIG.
[0078] In this case, in the core-shell particle form shown in Figure 1, the second region may be distributed within the first region as well, or conversely, the first region may be distributed within the second region.
[0079] 1 and 2, a form in which rod-shaped (or spherical) precipitates are distributed in a ring shape centered on the center of the particle is often observed in the first particle 100 and the second particle 200. The size of each precipitate is, for example, in the range of 0.1 μm to 2 μm.
[0080] According to the analysis by the present inventors, such precipitates are composed of an oxide of aluminum or a composite oxide of aluminum and metal M. Furthermore, according to the analysis by the present inventors, it has been found that such precipitates are likely to be formed when the first particles 100 and the second particles 200 are iron-aluminum alloy particles and are produced by a calorification treatment method as described below.
[0081] In addition, such precipitates act to suppress dislocation slippage, which is expected to lead to improved grain strength.
[0082] In addition to the above, various other forms are envisioned.
[0083] (Method of producing particles according to one embodiment of the present invention) Next, a method for producing particles according to one embodiment of the present invention will be described with reference to FIG.
[0084] FIG. 3 is a schematic diagram showing an example of the flow of a method for producing particles according to one embodiment of the present invention.
[0085] As shown in FIG. 3, the method for producing particles according to one embodiment of the present invention (hereinafter referred to as the "first production method") includes the following steps: A step (S110) of preparing mixed particles containing particles to be treated, an aluminum source, an activator, and a sintering inhibitor; A step (S120) of heating the mixed particles to calorify the treated particles; A step of removing the sintering inhibitor (S130); has.
[0086] Each step will be described in more detail below.
[0087] (Step S110) First, the mixed particles are prepared.
[0088] The mixed particles include the treated particles, the aluminum source, the activator, and the sintering inhibitor. Each of the particles will be described below.
[0089] (Particles to be treated) The particles to be treated are particles that are to be subjected to the calorification treatment.
[0090] The treated particles may include at least one element selected from the group consisting of, for example, iron (Fe), chromium (Cr), nickel (Ni), molybdenum (Mo), copper (Cu), manganese (Mn), tungsten (W), platinum (Pt), hafnium (Hf), zirconium (Zr), and cobalt (Co).
[0091] Furthermore, the particles to be treated are not limited to single metals, but may be alloys containing the above elements, for example, stainless steel particles or iron-aluminum alloy particles.
[0092] Furthermore, the treated particles may contain unavoidable impurities, such as phosphorus, sulfur, and carbon.
[0093] In the following description, for the sake of clarity, the first manufacturing method will be described using an example in which the treated particles are iron. The treated particles may contain inevitable impurities, such as manganese, phosphorus, sulfur, and carbon.
[0094] The average particle size of the treated particles is selected to be smaller than the average particle size of the sintering inhibitor described below. For example, the maximum particle size of the treated particles may be 0.29 times or less the average particle size of the sintering inhibitor.
[0095] The particle size of the particles to be treated may be in the range of 10 μm to 600 μm, for example.
[0096] In the present application, the "average particle size" is measured by the method specified in JIS Z 8801.
[0097] That is, sieves with different mesh sizes are stacked in several stages, starting with the smallest mesh size, and the particles to be measured are vibrated for a certain period of time with a certain amplitude to sieve them. Next, the mass of the particles remaining on each sieve is measured, and the particle size distribution of the particle mass is graphed. The particle size at which the cumulative value of the obtained particle size distribution corresponds to 50% is defined as the "average particle size."
[0098] However, the particle size of the treated particles is expressed as a range between a minimum value and a maximum value.
[0099] (Aluminum Source) The aluminum source may be aluminum metal particles, or aluminum alloy particles.
[0100] The average particle size of the aluminum source is selected to be smaller than the average particle size of the sintering inhibitor, for example, the average particle size of the aluminum source may be 0.29 times or less than the average particle size of the sintering inhibitor.
[0101] The average particle size of the aluminum source may be in the range of, for example, 10 μm to 600 μm.
[0102] The average particle size of the aluminum source is preferably smaller than the average particle size of the particles to be treated.
[0103] (Activator) The activator plays a role in forming metal halide vapor during the calorification of the particles to be treated, and in accelerating the calorification.
[0104] The activator includes, for example, at least one of ammonium chloride, iron chloride, aluminum chloride, iron fluoride, and aluminum fluoride. The activator is added, for example, in the range of 0.1% by mass to 2% by mass with respect to the entire mixed particles.
[0105] (Sintering prevention agent) The sintering inhibitor may include at least one of alumina, kaolin, and silicon oxide.
[0106] The sintering inhibitor may have at least one shape selected from the group consisting of, for example, a sphere, a triangular pyramid, a triangular prism, a tetrahedron, a cone, and a cylinder.
[0107] The sintering inhibitor has a sufficiently large average particle size compared to the treated particles and the aluminum source. For example, the average particle size of the sintering inhibitor is selected to be 3.4 times or more the maximum particle size of the treated particles and the average particle size of the aluminum source.
[0108] The average particle size of the sintering inhibitor may be, for example, in the range of 500 μm to 5000 μm.
[0109] (mixed particles) The above components are mixed to prepare mixed particles.
[0110] The amount of treated particles contained in the entire mixed particles is, for example, in the range of 10% by mass to 40% by mass. The amount of aluminum source contained in the entire mixed particles is, for example, in the range of 2% by mass to 20% by mass. The amount of sintering inhibitor contained in the entire mixed particles is, for example, in the range of 40% by mass to 80% by mass.
[0111] (Process S120) Next, the mixed particles prepared in step S110 are heat-treated. For this purpose, the mixed particles may be filled into a reaction vessel.
[0112] The reaction vessel is heated to perform a calorification process on the treated particles, that is, aluminum produced from the aluminum source diffuses and penetrates into the treated particles to form aluminum-infiltrated particles.
[0113] Here, the greater the difference in ionization tendency between the agent to be treated contained in the mixed particles and the aluminum source, the greater the amount of heat generated by the thermite reaction between the mixed particles when the reaction vessel is heated. This is because the aluminum reacts with the trace amount of oxygen contained in the treated particles to reduce the treated particles.
[0114] When such a thermite reaction occurs, the temperature inside the reaction vessel becomes extremely high, and the mixture after the treatment, i.e., the "treated mixture", becomes in the form of a mass in which all the particles are firmly bonded together. Furthermore, once such a mass of the treated mixture is produced, there may be a problem in that it becomes impossible to separate the sintering inhibitor from the treated mixture.
[0115] In contrast, in the first production method, the formation of a lump-like mixture can be significantly suppressed.
[0116] This feature will be described below with reference to FIG.
[0117] An example of the form of the mixed particles when they are filled in a reaction vessel is shown in Fig. 4. As shown in Fig. 4, the components of the mixed particles, that is, particles to be treated 352, aluminum source 354, activator, and sintering inhibitor 358, are each filled in the reaction vessel.
[0118] It should be noted that the activator is omitted in Fig. 4. Also, it is assumed here that each component of the mixed particles is spherical.
[0119] Here, the diameter (φ S ) is the diameter (φ Fe ) and the diameter (φ Al When the sintering prevention agent 358 has a thickness larger than the surface area of the sintering prevention agent 358, a gap 365 is generated between adjacent sintering prevention agents 358. The particles 352 to be treated and the aluminum source 354 are disposed in the gap 365 generated by the sintering prevention agent 358.
[0120] When the reaction vessel is heated with the mixed particles arranged in this manner, even if a thermite reaction occurs in the reaction vessel, the possibility that the treated particles 352 will adhere to the sintering inhibitor 358 and / or other treated particles 352 can be greatly reduced. This is because the voids 365 play a role in providing a large number of "small compartments" for reaction during the calorification process.
[0121] As a result, the treated mixture produced after the heat treatment is not in the form of an aggregated mass, but rather the aluminum-infiltrated particles and the sintering inhibitor 358 are separated from each other, making it possible to recover the aluminum-infiltrated particles from the treated mixture in a subsequent step.
[0122] Table 1 below shows examples of mixed particle packings that can achieve the above effects.
[0123] Here, the treated particles 352 are spherical iron particles (density 7.87 g / cm 3 ), and the aluminum source 354 is spherical aluminum particles (density 2.70 g / cm 3 ) and the activator was spherical ammonium chloride particles (density 1.527 g / cm 3 ), and the sintering inhibitor 358 was spherical alumina (density 4.00 g / cm 3 ) is assumed.
[0124] In addition, the average particle diameter φ of the sintering inhibitor 358 S is assumed to be 1000 μm, and the average particle diameter φ of the treated particles 352 is Fe is set to 10 μm to 600 μm, and the average particle diameter φ of the aluminum source 354 is set to 10 μm to 600 μm.Al is assumed to be 50 μm and the average particle size of the active agent is assumed to be 10 μm.
[0125] [Table 1] From Table 1, when 10 kg of sintering prevention agent 358 is closely packed, 74% of the total space volume is occupied by sintering prevention agent 358. Therefore, voids 365 are 26%.
[0126] If the entire void 365 (100%) is filled with the particles to be treated 352, the aluminum source 354, and the activator, then, as an example, the amount of the particles to be treated 352 would be 2.216 kg, the amount of the aluminum source 354 would be 1.491 kg, and the amount of the activator would be 0.067 kg.
[0127] Similarly, if 85% of the void 365 is filled with the treated particles 352, the aluminum source 354, and the activator, the amount of treated particles 352 can be calculated to be 1.879 kg, the amount of aluminum source 354 to be 1.253 kg, and the amount of activator to be 0.066 kg.
[0128] In the above calculation, the Al / Fe ratio in the mixed particles is assumed to be 40 / 60 (mass ratio), and the amount of the activator is assumed to be 0.5 wt% of the total.
[0129] If the sintering inhibitor 358 is packed in a manner other than close packing, the amount of each component can be calculated in a similar manner.
[0130] When the sintering prevention agent 358 is spherical, in order to obtain the above-mentioned effect, the packing rate of the sintering prevention agent 358 is preferably in the range of 55% to 74% (when packed most densely).
[0131] Moreover, the filling rate of the particles to be treated 352, the aluminum source 354, and the activator in the gaps 365 generated by the sintering inhibitor 358 is preferably in the range of 60% to 100%.
[0132] However, in practice, since it is assumed that the sintering prevention agent 358 may be non-spherical, the preferred range of the filling rate of the sintering prevention agent 358 is assumed to be 50% to 80%.
[0133] In this manner, in the first manufacturing method, the gaps 365 formed between the sintering inhibitors 358 can be utilized to perform the calorification treatment of the particles 352 to be treated.
[0134] The treatment atmosphere for the calorification treatment may be an inert atmosphere that does not contain oxygen, such as an argon gas atmosphere.
[0135] The treatment temperature is not particularly limited as long as the aluminum diffuses and penetrates into the treated particles. The treatment temperature may be in the range of 800°C to 1100°C, for example.
[0136] The treatment time is not particularly limited, but is, for example, in the range of 1 hour to 10 hours.
[0137] In this way, the first manufacturing method can properly perform the calorification process on the treated particles, and therefore can properly manufacture the particles according to one embodiment of the present invention having the above-mentioned characteristics.
[0138] (Step S130) The sintering inhibitor is then removed from the powdered treated mixture formed in step S120. The sintering inhibitor may be removed, for example, by sieving the treated mixture using a sieve that allows only particles with a small average particle size to pass through.
[0139] As described above, in the first production method, it is possible to significantly prevent the reaction system from becoming too hot due to the accumulation of excess heat that can be generated in the thermite reaction.
[0140] Therefore, in the first manufacturing method, the sintering inhibitor and the aluminum-infiltrated particles can be separated relatively easily.
[0141] By the above steps, the first production method can produce primary particles containing two types of aluminum alloy phases.
[0142] In the above description, the production method has been mainly described using iron-aluminum alloy particles as an example, but it will be apparent to those skilled in the art that aluminum alloy particles of other systems can also be produced by the same method. EXAMPLES
[0143] Examples of the present invention will now be described.
[0144] (Example 1) Calorified iron particles were prepared by the following method.
[0145] First, iron particles (13.20 mass%) as particles to be treated, aluminum particles (9.96 mass%) as an aluminum source, ammonium chloride particles (0.5 mass%) as an activator, and spherical alumina particles (76.34 mass%) as a sintering inhibitor were thoroughly mixed to prepare mixed particles.
[0146] The iron particles had a particle size of 38 μm to 75 μm, the aluminum particles had an average particle size of 50 μm, the activator had a particle size of 10 μm, and the alumina particles had a particle size of 1000 μm.
[0147] The mixed particles were packed into a heat-resistant container. The calculated packing rate of the alumina particles was 74%. The iron particles, aluminum particles, and ammonium chloride particles were packed so as to occupy 85% of the remaining 26% of voids.
[0148] Next, the atmosphere inside the heat-resistant container was replaced with argon, and the heat-resistant container was then heated to 1000° C. After being held at 1000° C. for 10 hours, the heat-resistant container was cooled in the furnace.
[0149] Thereafter, the treated mixture was taken out of the heat-resistant container and sieved through a #32 mesh sieve to remove the alumina powder, thereby obtaining spherical particles (hereinafter referred to as "particles according to Example 1").
[0150] (Example 2) Calorized iron particles (hereinafter referred to as "particles according to Example 2") were produced in the same manner as in Example 1.
[0151] However, in this Example 2, the content of iron particles in the mixed particles was 14.24 mass %, the content of aluminum particles was 9.49 mass %, the content of ammonium chloride particles as an activator was 0.5 mass %, and the content of spherical alumina particles as a sintering inhibitor was 75.77 mass %.
[0152] Other conditions, such as the packing ratio of the alumina particles, were the same as in Example 1.
[0153] (Example 3) Calorized iron particles (hereinafter referred to as "particles according to Example 3") were produced in the same manner as in Example 1.
[0154] However, in this Example 3, the content of iron particles in the mixed particles was 15.71 mass %, the content of aluminum particles was 8.83 mass %, the content of ammonium chloride particles as an activator was 0.5 mass %, and the content of spherical alumina particles as a sintering inhibitor was 74.96 mass %.
[0155] Other conditions, such as the packing ratio of the alumina particles, were the same as in Example 1.
[0156] (Example 4) Calorized iron particles (hereinafter referred to as "particles according to Example 4") were produced in the same manner as in Example 1.
[0157] However, in this Example 4, the content of iron particles in the mixed particles was 16.87 mass %, the content of aluminum particles was 8.31 mass %, the content of ammonium chloride particles as an activator was 0.5 mass %, and the content of spherical alumina particles as a sintering inhibitor was 74.32 mass %.
[0158] Other conditions, such as the packing ratio of the alumina particles, were the same as in Example 1.
[0159] (Example 11) Calorified chromium particles were prepared in the following manner.
[0160] First, chromium particles (27.3 mass%) as particles to be treated, aluminum particles (18.2 mass%) as an aluminum source, ammonium chloride particles (0.5 mass%) as an activator, and spherical alumina particles (54.0 mass%) as a sintering inhibitor were thoroughly mixed to prepare mixed particles.
[0161] The chromium particles had a particle size of 75 μm to 180 μm, the aluminum particles had an average particle size of 50 μm, the activator had a particle size of 10 μm, and the alumina particles had a particle size of 1000 μm.
[0162] The mixed particles were packed into a heat-resistant container. The calculated packing rate of the alumina particles was 52%. The chromium particles, aluminum particles, and ammonium chloride particles were packed so as to occupy 86% of the remaining 48% of the voids.
[0163] Next, the atmosphere inside the heat-resistant container was replaced with argon, and the heat-resistant container was then heated to 1000° C. After being held at 1000° C. for 10 hours, the heat-resistant container was cooled in the furnace.
[0164] Thereafter, the treated mixture was taken out of the heat-resistant container and sieved through a #32 mesh sieve to remove the alumina powder, thereby obtaining spherical particles (hereinafter referred to as "particles according to Example 11").
[0165] (Example 12) Calorized chromium particles (hereinafter referred to as "particles according to Example 12") were prepared in the same manner as in Example 11.
[0166] However, in this Example 12, the content of chromium particles in the mixed particles was 30.3 mass %, the content of aluminum particles was 15.1 mass %, the content of ammonium chloride particles as an activator was 0.5 mass %, and the content of spherical alumina particles as a sintering inhibitor was 54.1 mass %.
[0167] The mixed particles were packed into a heat-resistant container. The calculated packing rate of the alumina particles was 53%. The chromium particles, aluminum particles, and ammonium chloride particles were packed so as to occupy 84% of the remaining 47% of the voids.
[0168] (Example 21) Calorified nickel particles were prepared by the following method.
[0169] First, nickel particles (28.2 mass%) as particles to be treated, aluminum particles (17.3 mass%) as an aluminum source, ammonium chloride particles (0.5 mass%) as an activator, and spherical alumina particles (54.0 mass%) as a sintering inhibitor were thoroughly mixed to prepare mixed particles.
[0170] The nickel particles had a particle size of 10 μm to 45 μm, the aluminum particles had an average particle size of 50 μm, the activator had a particle size of 10 μm, and the alumina particles had a particle size of 1000 μm.
[0171] The mixed particles were packed into a heat-resistant container. The calculated packing rate of the alumina particles was 54%. The nickel particles, aluminum particles, and ammonium chloride particles were packed so as to occupy 85% of the remaining 46% of the voids.
[0172] Next, the atmosphere inside the heat-resistant container was replaced with argon, and the heat-resistant container was then heated to 1000° C. After being held at 1000° C. for 10 hours, the heat-resistant container was cooled in the furnace.
[0173] Thereafter, the treated mixture was taken out of the heat-resistant container and sieved through a #32 mesh sieve to remove the alumina powder, thereby obtaining spherical particles (hereinafter referred to as "particles according to Example 21").
[0174] Table 2 below shows the content and particle size of each component contained in the mixed particles used in each example.
[0175] [Table 2] (Rating 1) The particles according to Examples 1 to 4 were used to observe the morphology of the particles.
[0176] (Cross-sectional analysis) Using the particles according to Examples 1 to 4, samples for cross-section observation were prepared by the following method.
[0177] First, multiple particles were embedded in a resin, the resin was cured, and then the resin was polished with abrasive paper and a buffing machine to reveal the cross-section of the particles.
[0178] The observation target was a particle having a "maximum cross section." Here, "maximum cross section" means a cross section passing through the center of a spherical particle. Therefore, the "maximum cross section" of a particle has substantially the same dimension as the diameter of the spherical particle.
[0179] Hereinafter, the spherical particles to be observed in the particles according to Examples 1 to 4 will be referred to as "Sample 1" to "Sample 4", respectively.
[0180] The cross-section of the spherical particles in each sample was observed by SEM, and the amounts of aluminum and iron contained in the cross-section of the spherical particles were evaluated by EDX analysis.
[0181] 5 to 8 show (a) cross sections of the spherical particles obtained in Samples 1 to 4, and (b) distribution of aluminum contained in the cross sections, respectively.
[0182] For example, Fig. 5 shows a cross section (Fig. 5(a)) of a spherical particle obtained in Sample 1, and the distribution of aluminum contained in the cross section (Fig. 5(b)). Fig. 6 shows a cross section (Fig. 6(a)) of a spherical particle obtained in Sample 2, and the distribution of aluminum contained in the cross section (Fig. 6(b)), and so on.
[0183] In each sample, the distribution of iron in the cross section was the inverse of the distribution of aluminum.
[0184] From Figures 5 to 8, it was confirmed that in all of Samples 1 to 4, regions with low aluminum content (first regions) and regions with high aluminum content (second regions) were mixed in the particles.
[0185] For example, from Fig. 5, it can be seen that Sample 1 has a core portion (first region) with a lower aluminum concentration and an outer layer portion (second region) with a higher aluminum concentration, as shown in Fig. 1 above. Also, from Figs. 7 and 8, it can be seen that Samples 3 and 4 have a morphology in which regions with low and high aluminum concentrations are arranged in a "patterned" manner, as shown in Fig. 2 above. Note that, as shown in Fig. 6, Sample 2 basically has a core-shell structure in which regions with high aluminum concentration surround regions with low aluminum concentration, but it was found that even in the core portion, the regions with high aluminum concentration are dispersed in an island-like manner.
[0186] In addition, as can be seen most clearly in Sample 4 (Figure 8(b)), a whitish ring-shaped precipitate is observed on the cross section of the particle. Analysis confirmed that this ring-shaped precipitate is an aluminum oxide or a composite oxide of aluminum and iron.
[0187] The amounts of iron and aluminum contained in the first region and the second region of each of Samples 1 to 4 were analyzed by EDX analysis.
[0188] The results obtained for Samples 1 to 4 are summarized in Table 3 below.
[0189] [Table 3] From this result and the above-mentioned EDX analysis result, it was found that in Samples 1 to 4, the first region was composed of a phase mainly made of FeAl, and the second region was composed of a phase mainly made of FeAl2.
[0190] Next, energy dispersive X-ray (EDX) analysis was performed on the cross-section obtained for each of Samples 1 to 4 to evaluate the concentrations of aluminum and iron contained in the entire cross-section of the particle.
[0191] Table 4 below summarizes the analytical results obtained for each sample.
[0192] [Table 4] From this result, it was confirmed that in Samples 1 to 4, the total amount of aluminum was within the range of 8 mass % to 50 mass %.
[0193] (Rating 2) Next, similar evaluations were performed on the particles of Examples 11 and 12, and Example 21. Hereinafter, the spherical particles to be observed in the particles of Examples 11, 12, and 21 will be referred to as "Sample 11," "Sample 12," and "Sample 21," respectively.
[0194] The cross sections of Samples 11, 12, and 21 were observed by SEM, and the amounts of aluminum and other metals contained in each cross section were evaluated by EDX analysis.
[0195] 9 to 11 show (a) the cross section of the spherical particles obtained in Samples 11, 12 and 21, and (b) the distribution of aluminum contained in the cross section.
[0196] In Samples 11 and 12, the distribution of chromium in the cross section was the inverse of the distribution of aluminum. Similarly, in Sample 21, the distribution of nickel in the cross section was the inverse of the distribution of aluminum.
[0197] From Figures 9 to 11, it was confirmed that in Samples 11, 12 and 21 as well, the particles contained a mixture of regions with low aluminum content (first regions) and regions with high aluminum content (second regions).
[0198] The amounts of chromium and aluminum contained in the first region and the second region of Sample 11 and Sample 12 were analyzed by EDX analysis.
[0199] Table 5 below summarizes the results obtained for Samples 11 and 12.
[0200] [Table 5] From this result and the above-mentioned EDX analysis result, it was found that in Sample 11 and Sample 12, the first region was composed of a phase mainly composed of Cr2Al, and the second region was composed of a phase mainly composed of Cr5Al8.
[0201] Energy dispersive X-ray (EDX) analysis was then performed on the cross sections obtained for Samples 11 and 12 to assess the concentrations of aluminum and chromium contained throughout the cross sections of the particles.
[0202] Table 6 below summarizes the analytical results obtained for each sample.
[0203] [Table 6] From this result, it was confirmed that in Sample 11 and Sample 12, the total amount of aluminum was within the range of 8 mass % to 50 mass %.
[0204] Furthermore, the amounts of nickel and aluminum contained in each of the first and second regions in Sample 21 were analyzed by EDX analysis.
[0205] Table 7 below summarizes the results obtained for Sample 21.
[0206] [Table 7] From this result and the above-mentioned EDX analysis result, it was found that in sample 21, the first region was composed of a phase mainly made of NiAl, and the second region was composed of a phase mainly made of Ni2Al3.
[0207] Energy dispersive X-ray (EDX) analysis was then performed on the cross-section obtained for Sample 21 to assess the concentration of aluminum and nickel throughout the cross-section of the particle.
[0208] Table 8 below shows the analytical results obtained for sample 21.
[0209] [Table 8] From this result, it was confirmed that the total amount of aluminum in Sample 21 was within the range of 8 mass % to 50 mass %. [Explanation of symbols]
[0210] 100 particles (first particle) 110 First Area 120 Second Area 200 particles (second particle) 210 First Area 220 Second Area 352 Particles to be treated 354 Aluminum Source 358 Sintering prevention agent 365 void
Claims
1. Particles comprising an aluminum alloy, the particles are primary particles, The primary particles are substantially spherical in shape with a dimensional difference in mutually perpendicular X-axis and Y-axis directions being within ±20%; Composition M x A y and M z A w wherein M is a metal other than Al, 0<x<1, 0<y<1, 0<z<1, 0<w<1, x / y≧1, z / w<1, x+y=1, z+w=1; Particles having an aluminum content in the range of 8% by mass to 50% by mass.
2. 2. The particle of claim 1, wherein M comprises at least one selected from the group consisting of iron (Fe), chromium (Cr), nickel (Ni), molybdenum (Mo), copper (Cu), manganese (Mn), tungsten (W), platinum (Pt), hafnium (Hf), zirconium (Zr), and cobalt (Co).
3. The M is Fe, The primary particles are FeAl phase and FeAl 2 3. The particle of claim 1 having a phase.
4. The M is Cr; The primary particles are Cr 2 Al phase and Cr 5 A 8 3. The particle of claim 1 having a phase.
5. The M is Ni; The primary particles are NiAl phase and Ni 2 A 3 3. The particle of claim 1 having a phase.
6. Particles according to any one of claims 1 to 5, having an average particle size in the range of 10 µm to 150 µm.
Citation Information
Patent Citations
Production of aluminum alloy powder
JP1989108305A
Spherical catalytic powder composed of nickel-aluminum alloy, sponge nickel catalyst composed thereof, and their manufacturing method
JP2001192701A
Alloy powder for antioxidation coating and alloy excellent in antioxidation property using the same
JP2014055325A
Treatment of metals for coating or activation
WO1991007242A1
High-temperature oxidation resistant rare-metal-free hard sintered body, and manufacturing method therefor
WO2016056487A1